Environmental microbiology reports (Society for Applied Microbiology and Blackwell Pub., 2009)
Environmental Microbiology Reports is an online only sister journal to the existing Environmental Microbiology, publishing papers that document a single important finding, described within only the shortest of text and accompanied by a minimal number of tables and figures.